Multi-targeting siRNA nanoparticles for simultaneous inhibition of PI3K and Rac1 in PTEN-deficient prostate cancer (vol 99, pg 196, 2021) - Kim, Min Ju; Kim, Hyosuk; Gao, Xueliang; Ryu, Ju Hee; Yang, Yoosoo; Kwon, Ick Chan; Roberts, Thomas M.; Kim, Sun Hwa (ELSEVIER SCIENCE INC, 2021)
The authors regret reporting an error in acknowledgement section in the publication “This study was supported by the Mid-career Researcher Program (NRF-2019R1A2C2010408) by the Ministry of Education, Science and Technology, Republic of Korea, and a grant (HI19C1234) of the Korea Health Technology R&D Project…” After careful inspection, the grant number HI19C1234 must be corrected to HI19C0753. The authors would like to apologise for any inconvenience caused. ？ 2021